1-Dodecyl-3-methyl-imidazolium Based Ionic Liquid as Additive for Electrophoretic Separation of Fluoroquinolones - Liu, Y.Y.; Song, A.Q.; Xiong, S.L.; Mu, X.Y.; Wang, A.M.; Qin, W.D. (Asian Journal of Chemistry, 2011)
In present studies, the influences of 1-dodecyl-3-methyl-imidazolium (C12MIM)-based ionic liquid on electrophoretic separation of zwitter ionic fluoroquinolones are presented. The mobilities of electroosmotic flow and fluoroquinolones increased with buffer concentration in the presence of the ionic liquid and variation in separation voltage also influenced the separation. Presence of 0.3 mmol L-1 C12MIM-OH in the buffer of 20 mmol L-1 tetraborate /10 mmol L-1 phosphate significantly improved the resolution of the fluoroquinolones without detectable loss in the UV detection sensitivity. The model fluoroquinolones were separated in 14 min with detection limits of 0.1-0.14 mg L-1. Present experiments suggest that C12MIM-based ionic liquid at sub-millimolar is an effective additive for capillary electrophoresis separation of fluoroquinolones.